2015
DOI: 10.15666/aeer/1304_925933
|View full text |Cite
|
Sign up to set email alerts
|

Do Weather and Moon Have Any Influence on Spotlighting Mammals? The Case of Hare in Upland Ecosystem

Abstract: Abstract. Nocturnal spotlight survey is a common census technique for many mammal species. The influence of abiotic factors may be essential for the appropriate design of censuses, however this method has not been examined sufficiently in relation to abiotic factors such as weather conditions and the moon. We tested their influence for a commonly counted species, the brown hare (Lepus europaeus). Spotlight surveys were conducted at certain night time and transects in three upland Mediterranean areas, at differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A possible reason for this is that both devices are equally influenced by vegetation obstruction. Several studies have demonstrated that FLIR and spotlights were negatively influenced by vegetation (Belant and Seamans 2000, Tizzani et al 2014, Sokos et al 2015, Gonzalez et al 2016, Vinson et al 2020). Gonzalez et al (2016) found that in dense vegetation, detection of koala Phascolarctos cinerus beyond 60 m was unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for this is that both devices are equally influenced by vegetation obstruction. Several studies have demonstrated that FLIR and spotlights were negatively influenced by vegetation (Belant and Seamans 2000, Tizzani et al 2014, Sokos et al 2015, Gonzalez et al 2016, Vinson et al 2020). Gonzalez et al (2016) found that in dense vegetation, detection of koala Phascolarctos cinerus beyond 60 m was unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…In the spotlight method, hares were counted from a 4-wheeled vehicle (see Sokos et al. 2015 , for a detailed description).…”
Section: Methodsmentioning
confidence: 99%